If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 2) + -3 + 8 + 3(2x + 3) = 7 + 2 + -3 Reorder the terms: 5(2 + 2x) + -3 + 8 + 3(2x + 3) = 7 + 2 + -3 (2 * 5 + 2x * 5) + -3 + 8 + 3(2x + 3) = 7 + 2 + -3 (10 + 10x) + -3 + 8 + 3(2x + 3) = 7 + 2 + -3 Reorder the terms: 10 + 10x + -3 + 8 + 3(3 + 2x) = 7 + 2 + -3 10 + 10x + -3 + 8 + (3 * 3 + 2x * 3) = 7 + 2 + -3 10 + 10x + -3 + 8 + (9 + 6x) = 7 + 2 + -3 Reorder the terms: 10 + -3 + 8 + 9 + 10x + 6x = 7 + 2 + -3 Combine like terms: 10 + -3 = 7 7 + 8 + 9 + 10x + 6x = 7 + 2 + -3 Combine like terms: 7 + 8 = 15 15 + 9 + 10x + 6x = 7 + 2 + -3 Combine like terms: 15 + 9 = 24 24 + 10x + 6x = 7 + 2 + -3 Combine like terms: 10x + 6x = 16x 24 + 16x = 7 + 2 + -3 Combine like terms: 7 + 2 = 9 24 + 16x = 9 + -3 Combine like terms: 9 + -3 = 6 24 + 16x = 6 Solving 24 + 16x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 16x = 6 + -24 Combine like terms: 24 + -24 = 0 0 + 16x = 6 + -24 16x = 6 + -24 Combine like terms: 6 + -24 = -18 16x = -18 Divide each side by '16'. x = -1.125 Simplifying x = -1.125
| a-(-2)= | | 15+15(_12)= | | 7(2x-3)+2(3x+3)=3-2+5 | | x^3+4x^2+31x-30=0 | | 3x+2y=285 | | (3x+1)(3x+1)(3x+1)(3x+1)= | | 3(7+2x)=5(2x+4x) | | 2x-3y=3x+8y | | -16+4x-7x=5-6x | | a-(b-(c+d))= | | 12p-(5+2p)= | | -6(5k+4)=-144 | | (2x-3)(2x-3)(2x-3)= | | 62x+44+2x=-20 | | (3x+y)(3x+y)(3x+y)= | | 2x-x-14=0 | | 125x^6+27y^3= | | (3*3*3*3)-79=2 | | 3x^2-79=2 | | (x-5)(x+8)=10 | | (2x^2+3)+(4x^3+1)= | | y=x^4tan(5x) | | (X+y)-6x+8y= | | 2-x=x^2 | | (X+y)-2(3x-4y+3)= | | 5k-3(b+3k)-3b= | | a+3(2a-3b+c)+7c= | | P=3m+21 | | 3(5x-4y)-2(x-4y)= | | cos(2x)-sen(2x)=senx | | 2[x+4]=20 | | x^3+4x^2-4x=0 |